Utilization of treated industrial wastewater and accumulation of heavy metals in soil and okra vegetable - Aijaz Panhwar; Khalida Faryal; Aftab Kandhro; Shahid Bhutto; Uzma Rashid; Nusrat Jalbani; Razia Sultana; Aijaz Solangi; Mehtab Ahmed; Sofia Qaisar; Zain Solangi; Mudasir Gorar; et al. (Environmental Challenges, 2022)
Industrial wastewater pollution is the biggest threat to our environment. The current study deals with the consumption of treated industrial wastewater for cultivation purposes. During this study okra (Bhindi, local name) was cultivated with fresh water, industrial wastewater, and treated industrial wastewater. Three plots of 10 × 10 feet were sown with a total of 96 okra seeds. The highest height of 180 cm was found in the Okra plant grown on treated industrial wastewater while the lowest height recorded was 17 cm grown on industrial wastewater after three months.  It was found that treated industrial wastewater has a better and substantial impact on the growth of plants. The heavy metals i.e. zinc, iron, chromium, and copper, found in okra samples were within limits except chromium (1.8 mg/kg) in okra vegetable from plot-2; while these parameters zinc, iron, chromium, and copper, were found in soil, stem, and leaves. The treated industrial wastewater for agriculture purposes may be the biggest and useful source in the future, which will reduce the burden on freshwater resources and contribution to environmental protection. However, it is suggested that further research is needed to unveil complete nutritional and toxicological levels in okra edible vegetables.